OBAMA (OPTIMALISASI BAHAN BAKU MANIK-MANIK KACA) SEBAGAI SOLUSI SENTRA UKM MANIK-MANIK JOMBANG - Khofsoh, Afida; Torimtubun, Alfonsina Abat Amelenan; Nurmawati, Ardika; Fridayanti, Mutia Dhana (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Plumbon Gambang Jombang known as a center for craft beads SMEs (Small Medium Enterprises) in Indonesia. The problem faced by SMEs is the need for raw materials are depleted Duralex. As for the glass waste from cups, plates and other can not be formed (hard) not like Duralex glass. It is necessary for designing technologies for the sustainable raw material beads tens of SMEs in Plumbon Gambang. This program will result in the design of raw materials back, without using Duralex glass former but using ordinary glass and fused alumina as a softener and bleach with the composition of cullet (broken glass) 92% by weight of alumina and 8%, both of which are easily obtainable materials. With this program can ease the burden on small industries in order to increase revenue and continuity of production capacity as well as a discourse for small industries. Based on the analysis, the economic potential of the resulting products can compete with previously. Viewed from the side of science and technology, there are two value-added, technology design that is appropriate raw materials and the utilization of waste glass as the embodiment of green product. The method used was a survey, identification of problems, the study of literature, designing the composition of raw materials, the manufacture of glass beads, prototype testing, manufacturing and evaluation modules. From the results of this program concluded that the composition of the raw materials that are designed to have a soft structure and has enough color and strength. Keywords: Glass beads, Cullet, OBAMA